Influence of Electrode Material on the Electrical Discharge Plasma Generation and its Application in Seed Germination Enhancement - MUHAMAD FARID, MUHAMMAD AMMAR FATYHIN; Sahari, Norain (Progress in Engineering Application and Technology, 2024)
This study investigates the influence of electrode materials, specially copper and aluminium, on dielectric barrier discharge (DBD) plasma generation and its application in enhancing seed germination rates of mung bean (Vigna radiata). Futhermore, understanding the interaction between electrode materials and electrical parameters is important to optimize the plasma treatment process, thus providing a potentially effective and sustainable method to increase agricultural productivity. Acrylic was used as the dielectric material in these air pressure experiments, which were powered by 240 V, 50Hz AC power source connected to a neon transformer. The impact of aluminium and copper electrodes electrical characteristics on the intensity and initiation of plasma were investigated. According to the results, seeds treated with plasma germination rates were much greater than those of untreated seeds. Copper electrodes proved to be more effective because of their higher electrical conductivity. Copper initiated plasma at 2.2 kV and intensified at 2.92 kV, whereas aluminium required 2.24 kV for initiation and reached maximum intensity at 3.0 kV. According to the study’s findings, copper electrodes produce plasma more steadily and effectively, which makes them more suited for use in agricultural applications that aim to improve seed germination.